An investigating the effect of using Lumachelle as a substitute of aggrigate in RCC - Mahmoud Miri (Iranian Society of Structrual Engineering (ISSE), 2019)
According to lack of sufficient fine aggregate in some coastal area, using of other aggregate material are advisable. In this experimental study use of Lumachelle as a substitute of fine aggregates and replacement of lime and pozzolan as a part of cement are investigated on roller compacted concrete (RCC). RCC samples carried out and cured according to the related standard and compressive strength, splitting tensile strength, permeability and water absorption are examined. Totally, 9 different RCC mixtures include control mixture, 4 different mixtures include lime ( 5%, 10%, 15% and 20% of cement weight) were used as partial replacement of cement, and 2 different mixtures include 10% and 20% of pozzolan , by cement weight, as partial replacement of cement, were tested. Based on the results, among 5, 10, 15 and 20% of the lime used in this study, the replacement of 5% lime lead 3% increase in compressive strength and 7 % increase of tensile strength and it could be advisable for using in RCC. Moreover, the use of 20% substitutive Taftan pozzolan in RCC mix design decreases 24% of compressive strength and 11% of tensile strength in the short time. Besides, it improves resistance to get equal resistance with control sample in long-term that lead in 22% decrease depth penetration and 5% decrease in water absorption compared to control sample. Therefore use of 15 to 20% of pozzolan are also advisable according to the obtained results.